2001
DOI: 10.1097/00007890-200105150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Xanthine Levels as Viability Predictor of Livers Procured From Non-Heart-Beating Donor Pigs1

Abstract: It is suggested that xanthine content in the donor is able to predict survival after transplantation. Xanthine is significantly involved in the hepatic lesion elicited by warm ischemia and subsequent ischemia-reperfusion associated to liver transplantation from a NHBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…It is suggested that graft viability does not depend on the availability of AMP to be rephosphorylated to ATP (30). In agreement with this idea, another protective effect of NR arises from the fact that NR significantly reduces the levels of hepatic xanthine ( Figure 1B) (15,22,31).…”
Section: Discussionmentioning
confidence: 65%
“…It is suggested that graft viability does not depend on the availability of AMP to be rephosphorylated to ATP (30). In agreement with this idea, another protective effect of NR arises from the fact that NR significantly reduces the levels of hepatic xanthine ( Figure 1B) (15,22,31).…”
Section: Discussionmentioning
confidence: 65%
“…The involvement of XOD in stress oxidative and hepatic injury associated with liver transplantation is well known (35,49,50). High levels of either hypoxanthine or xanthine have been considered as markers of low survival rates in liver transplantation (51)(52)(53). The benefits of ischemic preconditioning on xanthine/XOD have been previously reported (35,54).…”
Section: Discussionmentioning
confidence: 95%
“…66 In addition, other biomarkers, including xanthine, hypoxanthine, hyaluronic acid, and reduced glutathione have been suggested for the assessment of graft viability. [67][68][69][70][71] Therefore, evaluating these biomarkers in DCD liver grafts prior to implant would be helpful. However, some technical limitations (such as the inability to identify these biomarkers in peripheral body fluids), technical demands, and time constraints in the clinical setting preclude these biomarkers from being incorporated into current practice.…”
Section: Figure 2 Ex Vivo Normothermic Machine Perfusion Systemmentioning
confidence: 99%